Kierkegaard: North American Dissertations 1934-1973 in the Fields of Philosophy, Religion, and General Literature - Rohatyn, Dennis A. (KIERKEGAARDIANA, 1974)
Kierkegaard: North American Dissertations 1934-1973 in the Fields of Philosophy, Religion, and General Literature